Renal and adrenal masses containing fat at MRI: Proposed nomenclature by the society of abdominal radiology disease‐focused panel on renal cell carcinoma. Issue 4 (28th January 2019) - Schieda, Nicola; Davenport, Matthew S.; Pedrosa, Ivan; Shinagare, Atul; Chandarana, Hersch; Curci, Nicole; Doshi, Ankur; Israel, Gary; Remer, Erick; Wang, Jane; Silverman, Stuart G.
Abstract : This article proposes a consensus nomenclature for fat‐containing renal and adrenal masses at MRI to reduce variability, improve understanding, and enhance communication when describing imaging findings. The MRI appearance of "macroscopic fat" occurs due to a sufficient number of aggregated adipocytes and results in one or more of: 1) intratumoral signal intensity (SI) loss using fat‐suppression techniques, or 2) chemical shift artifact of the second kind causing linear or curvilinear India‐ink (etching) artifact within or at the periphery of a mass at macroscopic fat–water interfaces. "Macroscopic fat" is most commonly observed in adrenal myelolipoma and renal angiomyolipoma (AML) and only rarely encountered in other adrenal cortical tumors and renal cell carcinomas (RCC). Nonlinear noncurvilinear signal intensity loss on opposed‐phase (OP) compared with in‐phase (IP) chemical shift MRI (CSI) may be referred to as "microscopic fat" and is due to: a) an insufficient amount of adipocytes, or b) the presence of fat within tumor cells. Determining whether the signal intensity loss observed on CSI is due to insufficient adipocytes or fat within tumor cells cannot be accomplished using CSI alone; however, it can be inferred when other imaging features strongly suggest a particular diagnosis. Fat‐poor AML are homogeneously hypointense on T2 ‐weighted (T2 W) imaging and avidly enhancing; signal intensity loss at OP CSI is uncommon, but when present is usually focal and is caused by an insufficient number of adipocytes within adjacent voxels. Conversely, clear‐cell RCC are heterogeneously hyperintense on T2 W imaging and avidly enhancing, with the signal intensity loss observed on OP CSI being typically diffuse and due to fat within tumor cells. Adrenal adenomas, adrenal cortical carcinoma, and adrenal metastases from fat‐containing primary malignancies also show signal intensity loss on OP CSI due to fat within tumor cells and not from intratumoral adipocytes. Level of Evidence : 5 Technical Efficacy Stage : 3 J. Magn. Reson. Imaging 2019;49:917–926.